Interactions Between Mesoscale Eddies and Synoptic Oscillations in the Bay of Bengal During the Strong Monsoon of 2019. Issue 10 (19th October 2020) - Greaser, Samantha R.; Subrahmanyam, Bulusu; Trott, Corinne B.; Roman‐Stork, Heather L.
Abstract: The 2019 southwest monsoon season is the first strong monsoon in the last 25 years and occurred concurrently with a strong positive Indian Ocean Dipole (pIOD). Given these unique circumstances, we examine the mesoscale eddy field in the Bay of Bengal (BoB) during 2019 and the interactions between these eddies and 3–7‐day synoptic oscillations and tropical systems, which contribute to monsoon rainfall and modulate the active (wet) and break (dry) phases of the Indian monsoon. We find that there is a drastic difference in eddy characteristics between the western (80–90°E) and eastern (90–100°E) BoB, where eddies in the eastern BoB are dominated by coastal Kelvin wave (CKW) dynamics and topographical influences, and the eddies in the western BoB are more heavily modulated by East India Coastal Current dynamics. We further find that the pIOD increased the overall sea level in the BoB and modified CKW propagation in the BoB such that all eddy types had more positive sea level anomalies. We find that cyclonic eddies vary coherently with both upper ocean heat content and 3–7‐day bandpass filtered precipitation and that both the number of cyclonic eddies and eddy amplitude increase in coherence with precipitation and ocean heat content following the passage of a tropical system. These results suggest a strong relationship between cyclonic eddies and 3–7‐day atmospheric variability. Plain Language Summary: The 2019 southwest monsoon is the first strong monsoon since 1994 and also occurred during a strong positive Indian Ocean Dipole event. We analyze the mesoscale eddy field in the Bay of Bengal during 2019 and investigate the connection between these eddies and 3–7‐day synoptic oscillations, which control the active (flood) and break (drought) phases of the monsoon over India. We find that coastal Kelvin waves influence eddies in both the eastern and western Bay, but that ocean bottom topography and the western boundary current dominate each region's dynamics, respectively. The positive Indian Ocean Dipole heavily impacted the coastal Kelvin waves in 2019. 3–7‐day synoptic events were most closely associated with cyclonic eddies, especially in the western Bay. The number of eddies and eddy amplitudes both increased following the passage of a tropical system. We also recognized a tendency for the tropical systems in 2019 to pass over cyclonic eddies and intensify afterward. Our results suggest a strong relationship between 3–7‐day synoptic‐scale variability and cyclonic eddies in the Bay of Bengal. Key Points: Different dynamic processes dominate the eddy fields in the eastern and western Bay of Bengal, yielding drastically different eddy fields The 2019 positive Indian Ocean Dipole heavily impacted coastal Kelvin wave propagation and sea level anomalies in the Bay of Bengal There is a statistically significant relationship between 3–7‐day synoptic variability and cyclonic eddies